Campus Setting as Living Labs: Lessons from IPB University, Bogor, Indonesia - Arif Satria; Alim Setiawan Slamet; Akhmad Kosasih; Agus Purwito; Iskandar Z Siregar; Heriansyah Putra (Journal of Sustainability Perspectives, 2023)
IPB University in Bogor, Indonesia, has developed its campuses as living laboratories for education, research, community outreach, innovation, and business. The university's infrastructure under the living lab concept, such as forestlands, farmlands, wetlands, teaching factories, and business units, offer real-life opportunities for students and staff to create greater impacts to societies from their academic activities. This paper presents the lessons learned from IPB's campus setting as a living lab, focusing on how students and stakeholders can learn from the existing infrastructure and facilities, how research can benefit from a natural setting, and how the campus can serve as a model for sustainable living. Implementing living lab concept faces challenges as other new initiatives, particularly on the aspects of effective interdisciplinary works, formalizing the community of practices in which pool of experts are organized and knowledge management system is developed. In conclusion, in the era of emancipated learning implementation in Indonesia, IPB University's campus setting could provide a platform for facilitating activities related to science-practices/policy interface.